Partial Melting and Structural Disorder in Models of Irradiated Amorphous Ge2Sb2Te5 - Mocanu, Felix C.; Elliott, Stephen R.; Konstantinou, Konstantinos (Wiley, 2025)
Identifying the link between the energy landscape that arises in chemically complex amorphous solids and the evolution of the structural disorder in the host glassy matrix upon ion irradiation can provide a fundamental understanding needed for the development of functional materials with enhanced radiation tolerance. Herein, a comprehensive analysis of the structural transformations that occur when an amorphous phase-change memory material is exposed to radiation-damage events is presented. Different measures of atomic-structural (dis)order—geometric, topological, and chemical—are analyzed in models of irradiated glassy Ge2⁢Sb2⁢Te5. The modeling results demonstrate that the degree of chemical disorder is increased within the postirradiation recovered amorphous network of Ge2⁢Sb2⁢Te5, while local atomic environments with homopolar bonds are formed in the geometry of the irradiated structures, as a result of the primary knock-on atom simulations. The molecular dynamics trajectories of the high-energy nonequilibrium cascades indicate partial local melting of the glass structure. The simulated system can access liquid-like states in the energy landscape when irradiated, which lowers the energy barriers for local relaxation, leading to further atomic rearrangements and a structural recovery of the glass network. This observation provides an important insight into the radiation tolerance of these amorphous materials.